Imágenes obtenidas mediante tomografía espiral multicorte (TEM) en infecciones del sistema nervioso central, Instituto Nacional de Ciencias Neurológicas - Esteban Arias, Darío (2014)
The following images of spiral tomography (TEM) brain correspond to patients who have been treated at the National Institute of Neurological Sciences. The final diagnosis was verified in their clinical and / or by pathological diagnosis stories.